Justice of the court sentence - Bibilo, Valentina N. (Journal of the Belarusian State University. Law, 2020)
Justice of the court sentence is provided by the interaction of the social regulators of justice on criminal cases and depends on two factors, one of which is legislation, and the other is discretion of judge. Justice of the criminal procedure creates conditions for the fair sentence. Justice of the sentence is based on establishment of the legal truth.
Keywords: law; court; court sentence; justice; principles of law; morality; state